2013
DOI: 10.1371/journal.pone.0085022
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Novel Saccharomyces cerevisiae Strains for Bioethanol Active Dry Yeast (ADY) Production

Abstract: The application of active dry yeast (ADY) in bioethanol production simplifies operation processes and reduces the risk of bacterial contamination. In the present study, we constructed a novel ADY strain with improved stress tolerance and ethanol fermentation performances under stressful conditions. The industrial Saccharomyces cerevisiae strain ZTW1 showed excellent properties and thus subjected to a modified whole-genome shuffling (WGS) process to improve its ethanol titer, proliferation capability, and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Enrichment analysis showed that “Biosynthesis of secondary metabolites” (Map01110), “Chloroalkane and chloroalkene degradation” (Map00625), “Benzoate degradation” (Map00362) and “Aminobenzoate degradation”(Map00627) were enriched with statistical significance p -values less than 0.05 in module M4, M9, M10, and M10, respectively (Table 2 ). The “Biosynthesis of secondary metabolites” pathway contains many metabolites known to be related to stress conditions, such as D (+) trehalose involved in salt stress in cyanobacteria (Hagemann, 2011 ), ethanol resistance in E. coli (Wang et al, 2013 ) and S. cerevisiae (Zheng et al, 2013 ; Wang et al, 2014a ), and L -isoleucine and L -glutamic acid involved in ethanol tolerance in E. coli (Horinouchi et al, 2010 ; Wang et al, 2013 ). “Benzoate degradation” (Map00362) and “Aminobenzoate degradation” (Map00627) were enriched due to the same two metabolites, benzoic acid and benzene-1,2,4-triol.…”
Section: Resultsmentioning
confidence: 99%
“…Enrichment analysis showed that “Biosynthesis of secondary metabolites” (Map01110), “Chloroalkane and chloroalkene degradation” (Map00625), “Benzoate degradation” (Map00362) and “Aminobenzoate degradation”(Map00627) were enriched with statistical significance p -values less than 0.05 in module M4, M9, M10, and M10, respectively (Table 2 ). The “Biosynthesis of secondary metabolites” pathway contains many metabolites known to be related to stress conditions, such as D (+) trehalose involved in salt stress in cyanobacteria (Hagemann, 2011 ), ethanol resistance in E. coli (Wang et al, 2013 ) and S. cerevisiae (Zheng et al, 2013 ; Wang et al, 2014a ), and L -isoleucine and L -glutamic acid involved in ethanol tolerance in E. coli (Horinouchi et al, 2010 ; Wang et al, 2013 ). “Benzoate degradation” (Map00362) and “Aminobenzoate degradation” (Map00627) were enriched due to the same two metabolites, benzoic acid and benzene-1,2,4-triol.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, it is possible to carry out a prescreening by subjecting the hybrid population to a severe stress by plating the cells on medium that contains for instance high ethanol or acetic acid levels, conditions encountered during fermentation. Next, only fast-growing colonies are tested individually in small-scale fermentations, and only superior hybrids are used for a next round of shuffling (Shi et al ., 2009; Zheng et al ., 2011ab, 2013ab; Tao et al ., 2012). Other investigators have instead tried to first improve stress tolerance and found that hybrids generated after multiple rounds of genome shuffling and selection also showed increased general fermentation performance (Wei et al ., 2008; Cao et al ., 2009, 2010, 2012; Hou, 2009; Wang & Hou, 2010; Jingping et al ., 2012; Lu et al ., 2012; Wang et al ., 2012a).…”
Section: Natural and Artificial Diversitymentioning
confidence: 99%
“…Therefore, it is evident that commercial dried baker's yeast used in the present research is equally viable. It is also important to note that baker's yeast in fresh or dried form is traditionally used as a starter culture in bioethanol production due to its low cost, wide availability, resistance to bacterial contamination and simple usage [27,28]. In industrial bioethanol production the yeast biomass is recycled in order to reduce the costs and improve the process productivity.…”
Section: Validation Of Optimization Results and Selection Of The Ymentioning
confidence: 99%